pH-Controlled Chiral Packing and Self-Assembly of a Coumarin Tetrapeptide - Mason, McKensie L (Langmuir : the ACS journal of surfaces and colloids, 2019)
A coumarin-tetrapeptide conjugate, EFEK(DAC)-NH2 (1), is reported to undergo a pH-dependent interconversion between nanotubes and nanoribbons. An examination of zeta potential measurements, circular dichroism (CD) spectra, and microscopy imaging (transmission electron microscopy and atomic force microscopy) identified three different self-assembly regimes based on pH: (1) pH 2-5, positively charged, left-handed helical nanotubes; (2) pH 6-8, negatively charged, right-handed helical nanoribbons; and (3) pH ≥ 9.0, a monomeric/disassembled peptide. The nanotubes exhibited uniform diameters of 41 ± 5 nm and wall thicknesses of 4.8 ± 0.8 nm, whereas the nanoribbons existed as either flat or twisted sheets ranging in width from 11 to 60 nm with heights of 8 ± 1 nm. The UV-vis and CD spectra of the most common antiparallel, β-sheet conformation of 1-dimer were simulated at the B3LYP/def2svpd level of theory in implicit water. These studies indicated that the transition from nanotubes to nanoribbons was coupled to an M → P helical inversion of the coumarin packing orientation, respectively, within the nanostructures. The assembly process was driven by β-sheet aggregation and π-π interactions, leading to the formation of nanoribbons, which progressively wound into helical ribbons and laterally grew into smooth nanotubes as the pH decreased